Cryptococcus neoformans Prp8 Intein: An In Vivo Target-Based Drug Screening System in Saccharomyces cerevisiae to Identify Protein Splicing Inhibitors and Explore Its Dynamics - Fernandes, José Alex Lourenço; Zatti, Matheus da Silva; Arantes, Thales Domingos; Souza, Maria Fernanda Bezerra de; Santoni, Mariana Marchi [UNESP]; Rossi, Danuza; Zanelli, Cleslei Fernando [UNESP]; Liu, Xiang-Qin; Bagagli, Eduardo [UNESP]; Theodoro, Raquel Cordeiro (MDPI, 2022)
Inteins are genetic mobile elements that are inserted within protein-coding genes, which are usually housekeeping genes. They are transcribed and translated along with the host gene, then catalyze their own splicing out of the host protein, which assumes its functional conformation thereafter. As Prp8 inteins are found in several important fungal pathogens and are absent in mammals, they are considered potential therapeutic targets since inhibiting their splicing would selectively block the maturation of fungal proteins. We developed a target-based drug screening system to evaluate the splicing of Prp8 intein from the yeast pathogen Cryptococcus neoformans (CnePrp8i) using Saccharomyces cerevisiae Ura3 as a non-native host protein. In our heterologous system, intein splicing preserved the full functionality of Ura3. To validate the system for drug screening, we examined cisplatin, which has been described as an intein splicing inhibitor. By using our system, new potential protein splicing inhibitors may be identified and used, in the future, as a new class of drugs for mycosis treatment. Our system also greatly facilitates the visualization of CnePrp8i splicing dynamics in vivo.
Keywords: cisplatin; CnePrp8i; inhibitor screening; intein; novel drug target; protein splicing; Prp8; Ura3